The Effectiveness of a Training Program Based on Self-regulated Learning Strategies for Mathematics Department Students and Its Impact on Providing Them with the Skill of Diversifying Stimuli and Mathematical Excellence for Their Students - Ibrahim, Azhar Ali Hussein (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
This study investigates the efficacy of a self-regulated learning-based training program on mathematics education students' stimulus diversification skills and their pupils' mathematical excellence. The research addresses the critical need for enhancing teacher preparation in mathematics education to improve student outcomes. Using a partial control experimental design, the study involved 46 fourth-year mathematics education students from the University of Zakho and 247 seventh-grade pupils from six basic schools. The training program, implemented over 22 sessions, was based on self-regulated learning strategies. Data were collected through an observation form for stimulus diversification skills and a mathematical excellence test. Results revealed significant improvements in the experimental group's stimulus diversification skills (t = 9.958, p < 0.05, η² = 0.68) and their pupils' mathematical excellence (z = 12.897, p < 0.05, η² = 0.53). These findings demonstrate the program's substantial impact on teacher competence and student achievement. The study concludes that integrating self-regulated learning strategies into mathematics teacher preparation can significantly enhance instructional quality and student performance in mathematics.